Assessment of pH-shift drug interactions of palbociclib by in vitro micro-dissolution in bio relevant media: An analytical QbD-driven RP-HPLC method optimization - Prajakta Harish Patil, Mrunal Desai, Rajat Radhakrishna Rao, Srinivas Mutalik, Gurupur Gautham Shenoy, Mahadev Rao, Puralae Channabasavaiah Jagadish (Journal of Applied Pharmaceutical Science, 2022)
In the present study, pH-dependent solubility and dissolution of Palbociclib (PB), a weakly basic cyclin-dependent kinase 4/6 inhibitor was investigated by application of analytical quality by design (QbD) approach to an reverse phase high performance liquid chromatography (RP-HPLC) method. An integrated analytical QbD approach for quantification of PB using RP-HPLC was designed by three-level three factorial, Box–Behnken design with numerical and graphical optimization. In vitro micro-dissolution, pH-shift experiments in bio-relevant media were carried out to predict PB’s pH-dependent drug-drug interaction (DDI) behavior. RP-HPLC method developed utilizing a Box– Behnken three-stage three factorial design was shown to be specific towards PB. The optimized method leads to effective and faster chromatographic separation of PB with lower retention time value together with a satisfactory peak symmetry and low peak tailing. Based on in vitro micro-dissolution studies, it was observed that PB has a typical weak base pH-dependent solubility characteristic and dissolution behavior with its release ranging from 98.96% to 102.66% in simulated gastric fluid pH 1.2 before dropping to 43.43% by addition of fasted state simulated intestinal fluid pH 6.5. Overall, our findings demonstrated that in vitro micro-dissolution approaches may accurately predict the intensity of pH-dependent DDI and that the use of these techniques prior to clinical DDIs studies might allow for adequate prediction of pH-dependent drug absorption in vivo.
Keywords: Acid-reducing agents, AQbD, CDK inhibitor, micro-dissolution, pH-dependent drug-drug interaction, RP-HPLC